11‐1: High Reliability Flexible AMOLED Display with Algorithm Compensation for Automotive Application. Issue 1 (25th September 2020) - Mou, Xin; Xiang, Lian; Wang, Gang; Huang, Xing; Liang, Cuicui; Chen, Guowei; Zhang, Lin; Li, Suncun; He, Xueying; Hu, Wenjie; Yang, Kai; Yu, Zhengmao; et al.
Abstract : In this paper, IR‐drop, de‐mura and burn‐in compensation algorithms were developed and implemented in TCON IC to improve the Long Range Uniformity (LRU), display mura and burn in issue. By implemented these algorithms, the LRU were improved from 75.5% to 94.5%, the mura and burn in level were decreased from level 4 to level 1. Moreover, automotive grade reliability was passed for 12.3 inch FHD flexible AMOLED display intergraded with GOA technology and TCON driving circuit board.